CBMP Five Year Implementation Plan: Developing an Integrated and Sustained Arctic Biodiversity Monitoring Network - Gill, Michael; Barry, Tom (Conservation of Arctic Flora and Fauna (CAFF), 2008)
A Supporting Publication to the Circumpolar Biodiversity Monitoring Program Framework Document Prepared by Michael Gill, Martin Raillard, Christoph Zckler, and Risa Smith. CAFF Designated Agencies: • Environment Canada, Ottawa, Canada • Finnish Ministry of the Environment, Helsinki, Finland • Ministry of the Environment and Nature, Greenland Homerule, Greenland (Kingdom of Denmark) • Faroese Museum of Natural History, Tórshavn, Faroe Islands (Kingdom of Denmark) • Icelandic Institute of Natural History, Reykjavik, Iceland • Directorate for Nature Management, Trondheim, Norway • Russian Federation Ministry of Natural Resources, Moscow, Russia • Swedish Environmental Protection Agency, Stockholm, Sweden • United States Department of the Interior, Fish and Wildlife Service, Anchorage, Alaska Description of the main activities and focus of the Circumpolar Biodiversity Monitoring Program (CBMP) from March 2008-2013.